Optical coherence tomography in the diagnosis of optic disc pit maculopathy – a review of literature - Kal, Magdalena; Winiarczyk, Mateusz; Płatkowska-Adamska, Bernadetta; Mackiewicz, Jerzy; Odrobina, Dominik (Medical Studies/Studia Medyczne, 2022)
An optic disc pit (ODP) is a congenital anomaly of the optic disc. This disorder may cause no symptoms and be diagnosed incidentally. However, in 25–50% of cases, it is accompanied by maculopathy causing a permanent reduction in visual acuity. Optical coherence tomography is a non-invasive technique that allows detailed diagnosis and monitoring the progression of the pathology mentioned above. In ODP complicated by maculopathy, OCT visualises exudative macular detachment with the dissection of the inner retinal layers followed by detachment of the outer retinal layers. It can also reveal complications such as full-thickness macular hole and subretinal haemorrhage, which also reduce visual acuity in patients with ODP.